Serum Levels of Lipopolysaccharide and 1,3-β-D-Glucan Refer to the Severity in Patients with Crohn’s Disease - Yanmin Guo; Guangxi Zhou; Chong He; Wenjing Yang; Zhenkun He; Zhanju Liu (Mediators of Inflammation)
Objectives. Interactions between the host and gut microbial community contribute to the pathogenesis of Crohn’s disease (CD). In this study, we aimed to detect lipopolysaccharide (LPS) and 1,3-β-D-glucan (BG) in the sera of CD patients and clarify the potential role in the diagnosis and therapeutic approaches. Materials and Methods. Serum samples were collected from 46 patients with active CD (A-CD), 22 CD patients at remission stage (R-CD), and 20 healthy controls, and the levels of LPS, BG, and TNF in sera were determined by ELISA. Moreover, sixteen patients with A-CD received anti-TNF monoclonal antibody therapy (infliximab, IFX) at a dose of 5 mg/kg body weight at weeks 0, 2, and 6, and the levels of LPS and BG were also tested at week 12 after the first intravenous infusion. Results. Serum levels of LPS and BG were found to be markedly increased in A-CD patients compared with R-CD patients and healthy controls (P<0.05). They were also observed to be positively correlated with CDAI, ESR, and SES-CD, respectively (P<0.05). Furthermore, the levels of TNF in sera had a significant correlation with LPS and BG, respectively. The concentrations of LPS and BG were demonstrated to be significantly downregulated in the sera of A-CD patients 12 weeks after IFX treatment (P<0.05), suggesting that blockade of TNF could inhibit bacterial endotoxin absorption, partially through improving intestinal mucosal barrier. Conclusions. Serum levels of LPS and BG are significantly increased in A-CD patients and positively correlated with the severity of the disease. Blockade of intestinal mucosal inflammation with IFX could reduce the levels of LPS and BG in sera. Therefore, this study has shed some light on measurement of serum LPS and BG in the diagnosis and treatment of CD patients.